Sintering-resistant high-efficiency biomass fuel - XIE XIUYUAN (2016)
The invention discloses a sintering-resistant high-efficiency biomass fuel which is prepared from the following raw materials in parts by mass: 18 to 22 parts of pulverized coal, 10 to 14 parts of soybean straw, 11 to 15 parts of turf, 18 to 23 parts of rice straw powder, 24 to 28 parts of corn stalk powder, 30 to 35 parts of wheat straw powder, 15 to 17 parts of robinia pseudoacacia wood chips, 19 to 25 parts of pine wood chips, 15 to 18 parts of sorghum stalks, 10 to 14 parts of cotton straws, 11 to 13 parts of willow scraps, 7 to 9 parts of peach wood chips, 12 to 16 parts of talc, 15 to 19 parts of sodium nitrate, 8 to 11 parts of paraffin, 22 to 26 parts of calcium carbonate and 16 to 20 parts of cyclopentane. The sintering-resistant high-efficiency biomass fuel disclosed by the invention has the advantages of sintering resistance, sufficient combustion, high heat, cleanness, no pollution, high efficiency, energy conservation and low manufacturing cost.